2019
DOI: 10.1177/1464884919861598
|View full text |Cite
|
Sign up to set email alerts
|

‘Our task is to demystify fears’: Analysing newsroom management of automation in journalism

Abstract: The study explores uses of algorithmic techniques in journalists’ working environments and investigates newsroom managers’ negotiations of automation as innovation process aimed at ensuring partial or full replacement of human labour with technology. Drawing from 15 qualitative interviews with representatives of newsroom management from legacy news institutions in the United Kingdom, Germany and the United States, the study analyses their (cl)aims to maintain the newsroom as a stable, but dynamic working envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…The broader notion of automated journalism is here preferred. Newsworkers themselves view the phenomenon of automation as encompassing various aspects of journalism such as data and information collection and content distribution (Milosavljević and Vobič, 2019a, 2019b; Wu et al, 2018); these findings are confirmed by the results of this study.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The broader notion of automated journalism is here preferred. Newsworkers themselves view the phenomenon of automation as encompassing various aspects of journalism such as data and information collection and content distribution (Milosavljević and Vobič, 2019a, 2019b; Wu et al, 2018); these findings are confirmed by the results of this study.…”
supporting
confidence: 86%
“…In recent research, the adoption and consequences of automation in journalism has been approached as technologically driven changes in processes of news production (Lindén, 2017a), as institutionally managed innovation processes (Milosavljević and Vobič, 2019b), and as a part of a broader transformation of journalism such as ‘computational journalism’ or a ‘quantitative turn’ (Anderson, 2012; Coddington, 2014). 1 It has been proposed that the prospects of automation pose an unprecedented challenge to our understanding of journalism as a human task (cf.…”
Section: Journalistic Agency In Transformation?mentioning
confidence: 99%
“…This is supported by Nam (2019) who reports that people aware of the impacts of automations on the labour market tend to be more optimistic and less sceptic. Milosavljević and Vobič (2019) investigate the fear of ATs of journalists in the United Kingdom, Germany, and the United States. The authors find that the journalists consider the new technologies as liberating rather than subordinating them.…”
Section: Fear Of Automationmentioning
confidence: 99%
“…As a mediator, his role was also to anticipate potential fears about the principle of automation, given the negative feelings that such a project is likely to entail. This position meets one of the biggest preoccupations that news automation managers have to challenge all along a process that is, first of all, human (Milosavljević and Vobić, 2019). His mixed background, between journalism and technology, enabled him to make dialogues easier between the newsroom and the start-up in charge of the development of "Quotebot".…”
Section: Leadership: the Socio-technical Mediatormentioning
confidence: 93%